A case of Citrobacter koseri renal abscess and review of the literature. (November 2022) - Hua, Duong Tommy; Lo, Jessica; Do, Huy Quang; Pham, Charles Dac
Citrobacter species are anaerobic gram-negative bacteria that are known to cause infections in immunocompromised hosts, particularly in hospital settings. Their opportunistic nature and tendency to develop antibiotic resistance make Citrobacter species challenging to treat. Renal or perinephric abscess formation as a result of Citrobacter infection is uncommon, having only previously been reported in four cases. We present a case of a 70-year-old man with diabetes and prostate cancer who was diagnosed with an 18 cm perinephric and a 10 cm perihepatic abscess caused by Citrobacter koseri . The patient required drains and re-positioning of the drains multiple times in addition to a prolonged course of antibiotics to achieve complete radiographic resolution. This case highlights the challenges in treating renal and perinephric abscess, as it required drain re-placements two additional times after the initial placement and an additional 4 weeks of antibiotics. Successful treatment for larger abscesses usually requires a two-arm approach, with antibiotics in combination with either percutaneous or surgical abscess drainage.